The application of pneumatic jigging in the recovery of metallic fraction from shredded printed wiring boards - Wang, Zheng; Hall, Philip; Miles, Nicholas J.; Wu, Tao; Lambert, Peter; Gu, Fu (SAGE Publications, 2015)
Waste electrical and electronic equipment (WEEE) is one of the fastest growing waste streams worldwide with volumes increasing by 40% each year. WEEE has attracted increasing concern worldwide due to its high metal content and the potential environmental threat which results from uncontrolled recycling practices. Innovative physical separation techniques for WEEE recycling are preferential compared with chemical methods because of the reduction of energy and chemical consumption as well as potential environmental threats. Pneumatic jigging is a dry separation process capable of achieving good separation of coarse material within a very narrow density range, which makes it suitable as a pretreatment process for WEEE recycling. The work presented in this paper investigates the potential application of pneumatic jigging in metal recovery from WEEE. A pilot scale pneumatic jig has been developed by University of Nottingham Ningbo to separate shredded printed wiring boards into two streams: a light fraction (mainly non-metallic fraction consisting of glass fiber, fluffs, and plastic pieces) and dense fraction (metallic fraction). The novelty of work presented in this paper is the application of a dry separation technique in WEEE recycling for metal recovery. Compared with conventional wet separation processes involved in WEEE recycling industry, dry separation has the advantage of zero secondary pollution. The results of this experimental program show pneumatic jigging to be an effective and environmental friendly technique as a pretreatment process for the recovery of the metallic fraction from shredded WEEE.